Influence of pulsating intracardiac blood flow on radiofrequency catheter ablation outcomes in an anatomy-based atrium model - Kaihao Gu; Shengjie Yan; Xiaomei Wu (International Journal of Hyperthermia)
Background Highly consistent cardiac ablation outcomes through radiofrequency catheter ablation (RFCA) under pulsatile and constant flow profiles (PP&CP) of intracardiac blood were previously indicated by computer modeling, with simplified geometry and lossless receipt of inflow for ablation catheters. This study aimed to further investigate the effects of intracardiac blood pulsatility in an anatomy-based atrium model.Methods Four pulmonary veins were blood inflows at 10 mm Hg. The mitral valve was the outflow, with PP based on pulsatile velocity curve from clinical measurements, and CP was obtained by averaging the velocity curve under PP over an ablation time of 30 s. A numerical comparison between ablation results under PP and CP, without experimental validation, was performed.Results Temperature fluctuations persisted in mid-myocardium, and most clearly in blood and endocardium under PP. At a constant power of 20 W, marked differences in ablation outcome between PP and CP occurred in the middle of unilateral pulmonary veins and the posterior wall of the left atrium (LA) where the blood velocities were significantly decreased under CP. The mid-myocardial, blood and endocardial temperatures, as well as the effective lesion volume at the former position, were decreased by 4.1%, 15%, 13.6%, and 13.8%, respectively under PP. The extents for the latter position were 11%, 22%, 22.5%, and 55.6%, respectively.Conclusion Intracardiac flow pulsatility causes a greater reduction in blood and endocardial temperatures at ablation sites away from the main bloodstream, effective cooling of which is more likely to rely on blood velocities approaching peak PP values.